The COVID-19 puzzle: deciphering pathophysiology and phenotypes of a new disease entity - Osuchowski, Marcin; Winkler, Martin Sebastian; Skirecki, Tomasz; Cajander, Sara; Shankar-Hari, Manu; Lachmann, Gunnar; Monneret, Guillaume; Venet, Fabienne; Bauer, Michael; Brunkhorst, Frank M; Weis, Sebastian; Garcia-Salido, Alberto; et al. (The lancet. Respiratory medicine, 2021)
The zoonotic SARS-CoV-2 virus that causes COVID-19 continues to spread worldwide, with devastating consequences. While the medical community has gained insight into the epidemiology of COVID-19, important questions remain about the clinical complexities and underlying mechanisms of disease phenotypes. Severe COVID-19 most commonly involves respiratory manifestations, although other systems are also affected, and acute disease is often followed by protracted complications. Such complex manifestations suggest that SARS-CoV-2 dysregulates the host response, triggering wide-ranging immuno-inflammatory, thrombotic, and parenchymal derangements. We review the intricacies of COVID-19 pathophysiology, its various phenotypes, and the anti-SARS-CoV-2 host response at the humoral and cellular levels. Some similarities exist between COVID-19 and respiratory failure of other origins, but evidence for many distinctive mechanistic features indicates that COVID-19 constitutes a new disease entity, with emerging data suggesting involvement of an endotheliopathy-centred pathophysiology. Further research, combining basic and clinical studies, is needed to advance understanding of pathophysiological mechanisms and to characterise immuno-inflammatory derangements across the range of phenotypes to enable optimum care for patients with COVID-19.